A hematologic scoring system and C-reactive protein compared to blood cultures for diagnosing bacterial neonatal sepsis - Deddy Eka Febri Liestiadi; Emil Azlin; Selvi Nafianti (Paediatrica Indonesiana, 2017)
Background Neonatal sepsis is the leading cause of death after pneumonia. Definitive bacterial sepsis diagnoses are made by blood culture results, which require a lengthy time. C-reactive protein (CRP) levels and a hematologic scoring system by Rodwell et al. are rapid tests that may be useful for diagnosing neonatal sepsis.                 Objective To determine the diagnostic value of CRP measurement and a hematologic scoring system compared to blood culture as the gold standard for diagnosing neonatal sepsis. Methods A cross-sectional study was conducted from April to August 2015 in the Neonatology Ward of Haji Adam Malik Hospital, Medan. A total of 43 neonates who were clinically suspected to have sepsis underwent CRP, hematologic scoring, and blood cultures. The IT ratio and procalcitonin indices were also examined. Diagnostic values were analyzed by a 2x2 table.Results Fourteen percent from all sample had positive bacterial culture. The CRP measurements had a sensitivity of 92.8%, specificity of 62%, positive predictive value (PPV) of 54.1%, negative predictive value (NPV) of 94.7%, positive likelihood ratio (PLR) of 2.44, and negative likelihood ratio (NLR) of 0.11. The hematologic scoring system had a sensitivity of 100%, specificity of 82.7%, PPV of 73.6%, NPV of 100%, PLR of 5.78, and NLR of 0. Procalcitonin and IT ratio show a good value of sensitivity and NPV, respectively. Conclusion The hematologic scoring system has better specificity than CRP measurement as compared to blood culture. However, both tests have good sensitivity for diagnosing neonatal sepsis.